Legal Analysis of Alleged Defamation Through Social Media Causing Harm to Others (Study of Central Jakarta District Court Decision Number 589/Pid.Sus/2024/PN Jkt.Pst) - Hestu Purwestri Kusumaningtyas; Abunawas, Abunawas; Jamiatur Robekha (SEAN Institute, 2025)
One form of unlawful acts that often occur in the development of technology and information in this digital era, is defamation or insults committed through social media. Defamation through social media is included in the category of cyber criminal acts regulated in Article 27 paragraph (3) of the ITE Law which reads: